Cognitive and Behavioral Symptoms in ALSFTD: Detection, Differentiation, and Progression. (January 2016) - Hsieh, Sharpley; Caga, Jashelle; Leslie, Felicity V. C.; Shibata, Marlene; Daveson, Naomi; Foxe, David; Ramsey, Eleanor; Lillo, Patricia; Ahmed, Rebekah M.; Devenney, Emma; Burrell, James R.; Hodges, John R.; et al.
Brief screening tools that detect and differentiate patients with amyotrophic lateral sclerosis and frontotemporal dementia (ALSFTD) from those more subtle cognitive or behavioral symptoms (ALS plus) and motor symptoms only (ALS pure) is pertinent in a clinical setting. The utility of 2 validated and data-driven tests (Mini-Addenbrooke's Cognitive Examination [M-ACE] and Motor Neuron Disease Behavioral Scale [MiND-B]) was investigated in 70 ALS patients (24 ALSFTD, 19 ALS plus, and 27 ALS pure). More than 90% of patients with ALSFTD scored at or below the cutoff on the M-ACE, whereas this was seen in only about 20% of ALS patients without dementia. The MiND-B differentiated between ALS pure and ALS plus diagnostic categories. Rasch modeling of M-ACE and MiND-B items revealed early cognitive (fluency, memory recall) and behavioral (apathy) symptoms in ALSFTD. The combined use of the M-ACE and MiND-B detects patients with ALSFTD, differentiates along the ALS continuum, and offers insight into the progression of nonmotor symptomatology in ALSFTD.